Communication in the middle school classroom: how the student understands the math teacher's speech (Research, Society and Development, 2019)
This study aims to analyze how the high school student understands the speech of the mathematics teacher in the classroom. We adopted a qualitative approach, whose data were obtained through video recordings of the classes and videotaped interviews of two public school teachers. In the data analysis, elements of Bakhtin's theory of language were used. In this study, we can not affirm that in fact there were situations in which teachers used a discursive genre provoking the student to interact with colleagues and participation in the classroom, however, we can affirm that in some moments situations occur that may implications in the students' comprehension process. It is possible to affirm that when one of the teachers makes a speech seeking to make comparisons, even relativizing the rigor of the mathematical language, there is the favoring of the comprehension of the teacher's discourse by the student. We also observe that the speech of a research interlocutor suggests that the researcher does not understand the discourse itself, by the way it performs it.